Transcriptional (p40x) and post-transcriptional (p27x-III) regulators are required for the expression and replication of human T-cell leukemia virus type I genes. - Inoue, J (1987)
The pX sequence of human T-cell leukemia virus type I codes for three products: p40x, p27x-III, and p21x-III. p40x is a transcriptional trans-activator that activates not only the viral long terminal repeat but also cellular genes for interleukin 2 and its receptor. p27x-III and p21x-III are not required for transcriptional activation, and their functions were unknown. Cotransfection experiments with defective human T-cell leukemia virus type I proviruses and various pX expression plasmids revealed that p27x-III, in addition to p40x, was required for gag gene expression. Furthermore, it was shown that p27x-III induced accumulation of a high level of unspliced viral gag mRNA. These results indicate that p27x-III is a post-transcriptional modulator of viral RNA whose transcription has been fully activated by p40x.